Clinical Holistic Medicine: Factors Influencing The Therapeutic Decision-Making. From Academic Knowledge to Emotional Intelligence and Spiritual “Crazy” Wisdom - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Scientific holistic medicine is built on holistic medical theory, on therapeutic and ethical principles. The rationale is that the therapist can take the patient into a state of salutogenesis, or existential healing, using his skills and knowledge. But how ever much we want to make therapy a science it remains partly an art, and the more developed the therapist becomes, the more of his/her decisions will be based on intuition, feeling and even inspiration that is more based on love and human concern and other spiritual motivations than on mental reason and rationality in a simple sense of the word. The provocative and paradoxal medieval western concept of the “truth telling clown”, or the eastern concepts of “crazy wisdom” and “holy madness” seems highly relevant here. The problem is how we can ethically justify this kind of highly “irrational” therapeutic behavior in the rational setting of a medical institution. We argue here that holistic therapy has a very high success rate and is doing no harm to the patient, and encourage therapists, psychiatrists, psychologist and other academically trained “helpers” to constantly measure their own success-rate. This paper discusses many of the important factors that influence clinical holistic decision-making. Sexuality could, as many psychoanalysts from Freud to Reich and Searles have believed, be the most healing power that exists and also the most difficult for the mind to comprehend, and thus the most “crazy-wise” tool of therapy.